2022
DOI: 10.1038/s41587-022-01486-w
|View full text |Cite
|
Sign up to set email alerts
|

Precision mitochondrial DNA editing with high-fidelity DddA-derived base editors

Abstract: Bacterial toxin DddA-derived cytosine base editors (DdCBEs)—composed of split DddAtox (a cytosine deaminase specific to double-stranded DNA), custom-designed TALE (transcription activator-like effector) DNA-binding proteins, and a uracil glycosylase inhibitor—enable mitochondrial DNA (mtDNA) editing in human cells, which may pave the way for therapeutic correction of pathogenic mtDNA mutations in patients. The utility of DdCBEs has been limited by off-target activity, which is probably caused by spontaneous as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…In contrast, analyses of nuclear off-target editing by enhanced DdCBEs [ 39 ], mDdCBEs [ 71 ], and mitoZFDs [ 58 ] have remained limited to targeted amplicon sequencing of a few predicted off-target sites. More fully assessing the levels and significance of these off-target edits is an important next step in the field, both in mtDNA and nDNA [ 39 , 57 , 58 , 63 , 71 , 72 ].…”
Section: Mitochondrial Base Editingmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, analyses of nuclear off-target editing by enhanced DdCBEs [ 39 ], mDdCBEs [ 71 ], and mitoZFDs [ 58 ] have remained limited to targeted amplicon sequencing of a few predicted off-target sites. More fully assessing the levels and significance of these off-target edits is an important next step in the field, both in mtDNA and nDNA [ 39 , 57 , 58 , 63 , 71 , 72 ].…”
Section: Mitochondrial Base Editingmentioning
confidence: 99%
“…Excessive imprecision of mtDNA base editing technologies has the potential to limit their use for disease modeling and therapeutic applications. Therefore, aiming to circumvent this constraint, Kim lab [ 72 ] developed high-fidelity DdCBEs (HiFi-DdCBEs), which relied on interface-engineered split DddA tox variants. Wild-type split DddA tox halves can spontaneously reassemble independently of TALE-DNA interactions, leading to unwanted off-target mutations in nDNA or mtDNA [ 57 , 72 ].…”
Section: Mitochondrial Base Editingmentioning
confidence: 99%
See 2 more Smart Citations
“…Lei et al demonstrated that fusing a nuclear export signal sequence (NES) can significantly reduce the genome-wide nuclear off-targets, and coexpression with a DddA inhibitor fused with nuclear localization signals (NLS) can eliminate both nuclear and mitochondrial off-targets with only a minor reduction in on-target efficiency . Lee et al created HiFi-DdCBEs by modifying amino acids around the binding interface between the two DddA halves, limiting functional deaminase activity to the intended target proximity and reducing collateral off-target changes …”
Section: Off-target Evaluation Of Tale-derived Base Editorsmentioning
confidence: 99%